The disappearing act eaudiobook A novel. - Steadman, Catherine (Random House Audio, 2021)
From the New York Times bestselling author of Something in the Water and Mr. Nobody comes “an unputdownable mystery about the nightmares that abound in the pursuit of Hollywood dreams” (Caroline Kepnes, author of the You series). “Stylish, riveting, hugely atmospheric—I couldn’t put it down.”—Lucy Foley, author of The Guest List A woman has gone missing. But did she ever really exist? A leading British actress hoping to make a splash in America flies to Los Angeles for the grueling gauntlet known as pilot season, a time when every network and film studio looking to fill the rosters of their new shows entice a fresh batch of young hopefuls—anxious, desperate, and willing to do whatever it takes to make it. Instead, Mia Eliot, a fish out of water in the ruthlessly competitive and faceless world of back-to-back auditioning, discovers the sinister side of Hollywood when she becomes the last person to see Emily, a newfound friend. Standing out in a conveyor-belt world of fellow aspiring stars, Emily mysteriously disappears following an audition, after asking Mia to do a simple favor. But nothing is simple. Nothing is as is seems. And nothing prepares Mia for a startling truth: In a city where dreams really do come true, nightmares can follow.